Inclusive Education: A Sociological Perspective in Realizing Equal Access to Education for Persons with Disabilities - Syah, Giant Ramadhan; Haryanto, Sigit; Fuadi, Djalal (Proceedings International Conference on Education Innovation and Social Science, 2025)
Inclusive education is an approach aimed at providing equal access to education for all individuals, including persons with disabilities. This article discusses the sociological perspective on inclusive education, highlighting the importance of equitable access to learning opportunities. Through analysis of current data and statistics, as well as case examples from various sources, this article seeks to identify the challenges and opportunities in implementing inclusive education in Indonesia. The findings indicate that despite some progress, there are still many obstacles to be overcome in achieving educational equality for persons with disabilities.